Investigation of corrosion behaviour of aluminium alloy 7075 processed by laser shock peening without coating - Shonhai, Natsai (University of the Witwatersrand, Johannesburg, 2024)
Laser shock peening (LSP) is a surface treatment to induce beneficial compressive residual stresses in metallic structures, thus improving their fatigue resistance. This technology has the potential to improve aeronautical component performance during application and maintenance. Aluminium alloys are used in the aviation industry due to their high strength-to-weight ratios and ease of design and manufacturing. However, they are susceptible to localised corrosion in some aggressive environments. This study investigated the corrosion behaviour of AA7075-T651 after LSP without a protective coating (LSPwC). Variations in power intensity (PI) of 1-6 GW/cm2, coverage (Np) of 2.5-67 spots/mm2 and spot size (SS) of 0.5-1.5 mm were explored. Surface modifications were evaluated using stereo microscopy, scanning electron microscopy (SEM), contact profilometry and Vickers microhardness tests. Three types of corrosion tests were conducted in 3.5 wt% NaCl solution on the peened and unpeened samples: potentiodynamic polarisation tests, 30-day immersion tests and stress corrosion cracking by three-point bending for 40 days. Microscopic examination revealed rough surfaces with areas of melting and solidification in LSPwC samples. Surface roughness increased in all samples post-LSPwC due to induced plastic deformation and surface ablation. Increasing PI and Np led to increased surface roughness. All peened samples had increased microhardness with a positive correlation with Np. Potentiodynamic polarisation revealed higher corrosion rates for most LSPwC samples, likely due to increased surface roughness which reduced corrosion resistance. Corrosion rate had a positive linear correlation with PI and Np with aluminium oxide formation and pitting as the dominant corrosion mechanisms. Improved corrosion resistance after LSPwC was observed in some samples with specific parameters. Notably, one sample had a corrosion rate four times lower than the unpeened one. The three-point bending induced tensile stresses on the peened surfaces, which led to the formation of multiple tangled cracks on the top surface of all specimens. The LSPwC samples were less susceptible to SCC and the best resistance was observed for Sample P3-SS1-Np50.38 which had no visible cracks in the sample cross-section.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Laser Shock Peening; Corrosion; SDG-7: Affordable and clean energy